Limbic Encephalitis following Allogeneic Hematopoietic Stem Cell Transplantation - Johansen, Silje; Kråkenes, Jostein; Vedeler, C. A.; Storstein, Anette Margrethe; Reikvam, Håkon (Case Reports in Immunology, 2022)
A woman with myelodysplastic syndrome (MDS) was treated with allogeneic hematopoietic stem cell transplantation (allo-HSCT). 65 days after the transplantation, she developed fatigue and central neurological symptoms. Clinical workup including magnetic resonance imaging (MRI) and cerebrospinal fluid (CSF) examination revealed findings suspicious for limbic encephalitis (LE), successfully treated with intravenous immunoglobulins and intravenous corticosteroids. Although a rare complication after allo-HSCT, physicians should be aware of neurological symptoms that develop throughout the transplantation course.